Evaluation of Consolidation of Holdings Programme Case Studies of Maharashtra, Punjab and Haryana, and Uttar Pradesh - Planning Commission (Planning Commission, 1970)
At the instance of the Planning Commission, the Programme Evaluation Organisation undertook an evaluation study of the Programme of Consolidation of Holdings. An integrated report on the basis of the sample of 18 districts, 36 tehsils/talukas, 106 villages and 1100 cultivators in 8 States was brought out in April, 1969.It was then proposed to bring out State reports in respect of a few selected States where large areas were consolidated. The present volume which consists of State reports for Maharashtra, Punjab and Haryana, and Uttar Pradesh brings out the peculiar problems obtaining In these States in greater detail. It is hoped that the findings and suggestions made in these reports would be useful to effect improvements, wherever necessary.
Programme Evaluation Organisation Planning Commission Government of India